EFFICACY AND SAFETY OF CHIMERIC ANTIGEN RECEPTOR-MODIFIED T CELL (CAR-T) THERAPY IN LYMPHOMA: AN UPDATED SYSTEMATIC REVIEW AND META-ANALYSIS - I Gede Krisna Arim Sadeva; I Gede Wikania Wira Wiguna; Ni Wayan Armerinayanti; Putu Mirah Wahyu Subagia Putri; Christo Timothy Mamangdean; Putu Ari Shanti Dewi; Kadek Meryndha Kumala Tungga; I Komang Raditya Putra Pratama; Agung Brahmanthya Nadine Kepakisan; Komang Indra Parama Arta (Meditory : The Journal of Medical Laboratory, 2026)
Abstract Background: Lymphoma (Hodgkin and non-Hodgkin) is a malignancy of the lymphatic system, with global prevalence reaching 2.8% and mortality rates reaching 248,700 cases each year. Therefore, Chimeric Antigen Receptor-Modified T cell therapy (CAR-T) was developed as a new approach to improve survival rates in lymphoma patients. Objective: This study aimed to evaluate the efficacy and safety of CAR-T cell therapy in lymphoma. Methods: PRISMA 2020 was used in the literature search and systematic review with the keywords "CAR-T Cell Therapy" and "Lymphoma". All statistical analyses were performed with R statistical software version 3.3 and MedCalc software version 22. A p-value ≤ 0.05 was considered statistically significant. Results: There were 16 studies involving 440 patients with lymphoma. The complete response rate was 62% (95% CI 55%-65%, I² = 40%). Meanwhile, cytokine release syndrome (CRS) occurred in 73% of cases (95% CI 49%-88%, I² = 80%). The overall Immune effector cell-associated neurotoxicity syndrome (ICANS) rate was 17% (95% CI 9%-30%, I² = 66%). There is no significant publication bias in all analyses (p-value>0.05). However, these results need to be interpreted with caution, considering the high heterogeneity in the pooled analysis results (I² > 50%).